The molecular signature of heat stress in sweat reveals non-invasive biomarker candidates for health monitoring - Noé Brasier; Carmela Niederberger; Martina Zanella; Alaa Othman; Ralph Schlapbach; Laura Kunz; Antje Dittmann; Kelly Reeve; Michael Prummer; Jörg Goldhahn (Communications Biology)
Abstract Heat stress is a significant public health challenge that leads to an increased risk of serious health deterioration, injuries, and loss of economic productivity. While the gold standard for monitoring heat stress continues to remain with population-based measurements, a straight-forward person-centered approach is lacking. Sweat can supply a wealth of molecular information, ranging from protein levels to levels of metabolites; it is thus a promising monitoring biofluid. A thorough investigation of sweat’s molecular signature during heat stress is called for. We conducted a cross-over study on healthy participants with personalized heat-stress visits to investigate heat stress’s proteomic and molecular signatures in sweat. Through mass-spectrometry analysis, we identified multiple candidate biomarkers ranging from amino acids to microbiome metabolites and proteins. To the best of our knowledge, these biomarker candidates represent the first successful approach to metabolically differentiate between various heat stressors thereby enabling their acute monitoring. While these biomarker candidates need further investigation to confirm their clinical value, many have already been identified as directly associated with heat stress in animals and plants. Once further investigated, next-generation wearable devices for person-centered, on-skin sweat-analysing platforms could be developed that would transform health management during exposure to heat stress.